Atraktor Cumi-Cumi Yang Ramah Lingkungan Dan Bertanggung Jawab di Perairan Rigaih Kabupaten Aceh Jaya - Muhammad Rizal (Jurnal Marine Kreatif, 2017)
Utilization of fishery resources of squid through fishing activities is time to be accompanied by regulation of arrest and cultivation activities covering the effort of hatchery (hatchery) and release to nature. This effort can improve the damage of squid resources as it can be done to enrich the stock to improve and sustain the resources of the squid. One of the most important factors to support the cultivation of squid is egg supply and spawning success. The Rigaih area of Aceh Jaya Regency is one of the most diverse squid stock areas and is captured by local traditional fishermen every day. But until now there has been no cultivation and other activities related to maintaining the sustainability of squid. The purpose of this service is the difference of the type and depth of the waters where the installation of the attor to the attachment of squid eggs using black iron coated iron wire and the ijok rope tie in the waters of Rigaih Aceh Jaya Regency. The results obtained are the number of capsules produced in one spawning range 57 to 601 with the number of eggs contained in it as much as 124 to 1421 grains.